Cancer Incidence in Nigeria: A Tertiary Hospital Experience - Uchendu, Obiora Jude (Asian Pacific Journal of Cancer Care, 2020)
Background: Cancer is a poorly addressed major cause of morbidity and mortality in Nigeria. Aim: The study aims at analyzing the age, gender and topography of cancer in Delta State, Nigeria. Setting: The research was conducted in the State tertiary health care center, the major referral center in Delta State, Nigeria. Materials and Methods: This is a 6-year (2014-2019) descriptive retrospective study of all histologically diagnosed cancer cases in the department of Histopathology, DELSUTH. Results: Cancer accounted for 668 (28.9%) of the 2300 histologically diagnosed cases, involving 461 females and 207 males with mean ages of 48.40 and 54.14 respectively. The combined sex mean age and age range were 50.17 and 1-98 years respectively. The peak occurred in the 7th decade for males and the 6th decade for females. The most common cancers are breast (36.5%), colorectal (11.7%), prostate (8.1%) cervical (7.2), soft tissue (6%), non-melanoma skin (5.2%), ovarian (4%),metastatic (4%), gastric (2.6%), thyroid (1.8%), and salivary gland (1.4%) cancers. The peak incidence for breast and thyroid cancers; lymphomas; colorectal and cervical cancers; ovarian; and prostate cancers occurred in the 4th, 5th, 6th, 7th and 8th decades respectively. Conclusion: Cancer constitute a major disease burden, increases in incidence with age, and affects more females than males with breast, prostate, and colorectal cancers as most common cancers. Understanding the local epidemiological characteristic is fundamental to planning for proper preventive, diagnostic and therapeutic strategies.